Morte e ironia em Boa tarde às coisas aqui em baixo : diálogos com o barroco - Conrado, Luiza Minnemann (2011)
The present dissertation aims to analyze the novel Boa tarde às coisas aqui em baixo, by António Lobo Antunes, trying to understand in which way in it, as in many other 21st century literary works, we can find a dia log space with the baroque aesthetics. We will seek to estabilish, in this sence, relations between the baroque time and the present time, considering the similarities in terms of crises societies and in terms of artistics configuration. It will be explored ironic and alegoric writing configuration, and in the same way we will th to demonstrate that the obsession by the death idea, in it s multiple ways, cross all the novel relating in to the ruin idea.